Are Happy Seeder and PUSA Decomposer Potential Options for Sustainable Ways of Paddy Straw Management (Indian Journal of Extension Education, 2023)
The study was undertaken to assess the effect of in-situ paddy straw management by the adoption of Happy Seeder and PUSA decomposer on the profitability in wheat cultivation and constraints to the adoption of these technologies using primary data collected from randomly selected 121 farmers in the Karnal district of Haryana in the year 2022. The results showed that the adoption of these technologies has reduced the cost and increased the profitability in wheat cultivation. However, the adoption of these technologies especially among small farmers remains limited. Financial constraints to the adoption of Happy Seeder and the longer duration for the decomposition of straw by PUSA decomposer were reported to be major hindrances in their adoption. Educating the farmers regarding the consequences of stubble burning and the potential benefits of adopting these technologies and addressing financial constraints and improving the efficacy of PUSA decomposer may be the potential options for sustainable management of paddy straw.